Prediction of five-flavored pentaquarks - Chao-Wei Shen; Ulf-G. Meißner (Physics Letters B, 2022)
We analyze the possibility of the existence of a fully exotic pentaquark state udscb¯, which is made from the five different flavors participating in the strong interactions. We investigate the coupled channel effects of the B(⁎)Ξc(′) system through t-channel vector meson exchange to search for such states. A BΞc and a BΞc′ bound state are found to have binding energies of about 10−30 MeV with BsΛc and BcΛ being the possible decay channels. Similarly, a bound state is formed in the B⁎Ξc and B⁎Ξc′ channels, respectively. The properties of these states including pole positions, decay widths and couplings to other channels are extracted. These states could be searched for through the pp→BcΛX or pp→Bs(⁎)ΛcX processes by the LHCb collaboration.